Cadmium disrupted homeostasis of proximal renal tubular cells via targeting ATF4-CHOP complex into the nucleus - Muhammad Asmat Ullah Saleem; Ying-Xin Zhao; Farhat Bano; Yi-Xi Tang; Mu-Zi Li; Kanwar Kumar Malhi; Xiao-Wei Li; Xue-Nan Li; Yi Zhao; Jin-Long Li (Poultry Science)
Cadmium, a ubiquitous toxic metal and environmental pollutant, is associated with several renal metabolic disorders and disrupts the homeostasis of kidneys in humans and animals. However, the precise molecular mechanism remains poorly elucidated. The present study investigated the role of the ATF4-CHOP nuclear transcriptional axis and its interactions with cellular pathways in cadmium-induced nephrotoxicity. We acquired 120 one-day-old chickens, randomly divided them into four groups (Con, Cd35, Cd70, Cd140), and were treated with graded cadmium doses for 90 days. The kidney tissues were collected for comprehensive histopathological, biochemical, and molecular analyses using western blotting, qRT-PCR, immunofluorescence, and tunel assay. Subsequently, we revealed that cadmium exposure induced ER stress, significantly upregulated CHOP expression, and activated pro-apoptotic ATF4-CHOP axis. Our findings revealed a complex interplay, where ER stress activated inflammation. Concurrently, mitochondrial disruption elevated ROS production and oxidative stress, which impaired renal homeostasis. Moreover, inhibition of autophagy and mitophagy led to the accumulation of damaged cell organelles, further exacerbating apoptotic signaling. Our results elucidate that an integrated network of cellular stress pathways mediates cadmium-induced renal toxicity, with the ATF4-CHOP axis acting as a crucial pro-apoptotic pathway. This study provides critical insights into the mechanisms of cadmium-induced nephrotoxicity and potential therapeutic interventions to mitigate heavy metal-induced renal homeostasis disruption and renal damage.